2011
DOI: 10.1097/prs.0b013e31820cf4a6
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Vascularized Free Fibula Graft with an Arteriovenous Loop for Fusion of Cervical and Thoracic Spinal Defects in Previously Irradiated Pediatric Patients

Abstract: The free fibula flap is ideally suited for accelerated posterior spinal fusion after extensive resection of cervical or thoracic spinal neoplasms. An arteriovenous saphenous vein loop facilitates the microvascular anastomosis in this anatomical region that lacks suitable recipient vessels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 22 publications
0
24
0
Order By: Relevance
“…At present, the most effective method for treating bone defect is autologous bone grafting carrying blood vessel. 8,9 This method can prevent bone graft to be absorbed and could reconstruct blood supply permanently, but there are also some disadvantages related to this strategy including inadequate bone resource, limited bone shape, inducing some damage in the donor area, etc. It is to note that autologous bone grafting carrying blood vessel cannot repair the large bone defect.…”
Section: Introductionmentioning
confidence: 99%
“…At present, the most effective method for treating bone defect is autologous bone grafting carrying blood vessel. 8,9 This method can prevent bone graft to be absorbed and could reconstruct blood supply permanently, but there are also some disadvantages related to this strategy including inadequate bone resource, limited bone shape, inducing some damage in the donor area, etc. It is to note that autologous bone grafting carrying blood vessel cannot repair the large bone defect.…”
Section: Introductionmentioning
confidence: 99%
“…Lengthening with additional microanastomosis is a classical procedure. Vein grafting is also a conventional and useful technique (Flores, Rad, Shridharani, Stapleton, & Rosson, ; Karanas, Yim, Johannet, Hui, & Lineaweaver, ), and the vascular loop technique (Jandali, Diluna, Storm, & Low, ; Lind, McCarthy, Derman, & Jacobs, ) and arteriovenous interposition grafting (Echo & Bullocks, ; Zenn, Pribaz, & Walsh, ) is a modification of conventional vein grafting. Other new procedures are based on using the natural vascular branching pattern of the subscapular vascular tree (Usami, Okazaki, Tanaka, Homma, & Yano, ) or branches of the ALT flap (Huang, Hsieh, Lai, Lin, & Chang, ).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be considered that complication rates for this procedure are relatively high, and should be weighed against the potential benefit. 1,27,36,41,48,67 For instance, Minami et al 47 reported that the procedure had to be abandoned in 3 of 16 patients because of difficulties with microsurgical anastomosis. Also, the mean ± standard deviation time needed for the harvest, rib preparation, and anastomosis was 58 ± 13 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…58,62,63,66 Because of these issues, it is unclear what bone graft options should be selected in patients with spinal column tumors. The literature is also significantly limited, as a majority of prior reports were either retrospective with small numbers of patients, 1,36 or case reports, 5 focusing on survival outcomes or technical aspects of surgery rather than fusion outcomes. 73 To the best of our knowledge, this is the first systematic review and meta-analysis focusing solely on bone graft options and fusion rates in the setting of spinal column tumor resection, aiming to provide some clinical insight into this controversial issue.…”
mentioning
confidence: 99%